EKOLOGI HUTAN PAMAH BARITO ULU, KALIMANTAN TENGAH: RESPON TERHADAP PEMUPUKAN NITROGEN DAN FOSFOR - Mirmanto, Edi (BERITA BIOLOGI, 2001)
A fertilization was set up in September 1993 in species-rich dipterocarp forest in the Barito Ulu study site in Central Kalimantan.The experiment was unusual in that previously reported fertilizer experiments have been made in montane forest. The following treatments were applied: control, +N, +P and +NP. There were five blocks of four 50m x 50m plots with a separate treatment for each plot. Fine litterfall was collected on all of the plots from May 1994 for one year. There was evidence of higher litterfall quantities and increased of P and N in the litterfall. All trees (> 10 cm dbh) were measured in August 1993 and in July 1994 and there was a clear girth increment response of some dipterocarp species to +NP and small size of trees to +N.